Impact of temperature and forward osmosis membrane properties on the concentration polarization and specific energy consumption of hybrid desalination system - Goi, Yi Ken; Liang, Yong Yeow (Springer, 2024)
This study investigates how temperature and forward osmosis (FO) membrane properties, such as water permeability (A), solute permeability (B), and structural parameter (S), affect the specific energy consumption (SEC) of forward osmosis-reverse osmosis system. The results show that further SEC reduction beyond the water permeability of 3 LMH bar-1 is limited owing to high concentration polarization (CP). Increasing S by 10-fold increases FO recovery by 177.6%, causing SEC decreases by 33.6%. However, membrane with smaller S also increases external CP. To reduce SEC, future work should emphasize mixing strategies to reduce external CP. Furthermore, increasing the temperature from 10 to 40 °C can reduce SEC by 14.3%, highlighting the energy-saving potential of temperature-elevated systems. The factorial design indicates that at a lower temperature, increasing A and decreasing S have a more significant impact on reducing SEC. This underlines the importance of developing advanced FO membranes, particularly for lower-temperature processes.